Corrosion inhibition in self-compacting concrete - Blankson, Marva Angela (2013)
This research was undertaken to investigate the effectiveness of carboxylic corrosion inhibitor in fly ash and silica fume (respectively FM and SM) samples and nitrite-based corrosion inhibitors in fly ash (FGC) sample. The findings from this research show that the addition of the carboxylic inhibitor altered the hydration of fly ash and silica fume self-compaction concretes (SCCs) by delaying the formation of ettrngite and the production of portlandite in the FM and SM samples and ultimately causing the calcium aluminate hydrates to surround the fly ash and cement particles. It was shown that this resulted in slight setting retardation in the silica fume particles but significant delay in the hydration of the fly ash SCC. Further, this development brought about by the use of the carboxylic inhibitor contributed bleeding of different levels in the fly ash and silica fume samples and this condition was shown to increase the heterogeneity of the FM and SM SCCs. Although addition of the nitrite-based inhibitor retarded the setting of paste of the fly ash SCC, no noticeable delay in the hardening of the concrete was manifested. When the nitrite-based inhibitor was included in the fly ash SCC, the physical structure of the interfacial transition zone and the bulk of the mortar were found to be less porous and hence the concrete displayed a higher level of homogeneity.